Under What Conditions Can Regional Learning Promote Participation? Development, Testing, and Evaluation of a New Conception of Action-Oriented Learning in Regional Context – Regional Learning 21+ - Schockemöhle, Johanna (Journal of Geography Education, 2010)
Taking as a basis that on-site learning in the own region has a high educational potential and addressing the objective of promoting the participation of adults, young people and children at regional level, the concept of Regional Learning 21+ was developed, tested and evaluated in this research project. The evaluation results show that regional action-oriented learning promotes the identity formation and the acquisition of participatory competence, thus contributing effectively to the participation at regional level with particular emphasis on education for sustainable development. A two-group pre-test and post-test design was used to evaluate the effectiveness of Regional Learning 21+. Participants in learning activities were asked to complete a questionnaire before and after the activity in order to detect changes in the characteristics of regional identity and participatory competence. In addition, interviews with organizers of learning activities provided comprehensive data to identify factors that influence the effectiveness of the measure.